MULTIMODAL APPROACH TO THE STUDY OF SPECIALIZED TEXTS IN TECHNICAL DISCOURSE - Yuliia V. Polycheva; Volodymyr I. Vetokhin (Alfred Nobel University Journal of Philology, 2023)
The article aims to highlight the possibilities of a multimodal approach to the study of specialized texts in technical discourse. The research design for this study is analytical and descriptive, which focuses on a deductive narrative approach and a complex of complementary theoretical methods: analyzing, summarizing and interpreting scholarly sources on the issue under scrutiny; conceptual analysis of the term “multimodal approach”; analyzing multimodal elements of a technical text; distributional analysis – to find out the environment, which contains various multimodal components; monographic method – to interpret the results obtained in a coherent logical way. The theoretical significance of the article lies: firstly, in expanding the existing understanding of multimodality in linguistic studies at large and in modern technical discourse in particular; secondly, in applying multimodal analysis to the study of technical texts, which differs significantly from similar analyses of other types of discourse due to its powerful semiotic component. Its practical significance is determined by the identification of additional opportunities for linguists to analyze technical texts in terms of a multimodal approach. It is stated that a growing interest in multimodality from the linguistic point of view can be attributed to two main reasons. Firstly, in linguistics, there has been a general turn to functional pragmatism, in particular, to the study of linguistic performance, including the interaction of sociocultural and cognitive factors of speech activity. Secondly, significant changes have also occurred in the field of speech practice: mediated, multi-channel communication in nature, based on the convergence of the semiotic resources available, has come to the fore. The principles of the multimodal approach and a model for conducting a multimodal analysis of a text are considered. As mentioned in the article, the multimodal approach can be applied to analyzing all types and forms of communication, including the analysis of texts, including technical ones, in which two or more semiotic resources are integrated and interact to realize the communicative functions of the text. A multimodal technical text is viewed as a special linguistic and visual phenomenon, where linguistic and extralinguistic means form a common semantic field, have a complex impact on the addressee of these texts. These texts demonstrate the diversity and complexity of approaches to expressing the content and achieving the communicative goal of the message, where, along with verbal elements, non-verbal ones are integral, in particular, illustrations, diagrams, graphs and schemes. On the whole, visual content plays an extremely important role in written technical communication. The image is the most important part of multimodal technical texts and carries a significant functional load, providing a more complete, comprehensive perception. Also, among the main and most important elements of multimodal texts, color and signature stand out. Given that, a distinctive feature of multimodal technical discourse is the presence of accompanying drawings or / and explanatory drawings, which demonstrate all the geometric parameters and other information concerning the manufacturing processes of the product. From an extralinguistic point of view, it is not the language that is considered, but a drawing, a table, a diagram as a whole, creating an image and representing encrypted data, the correct analysis of which reveals a large layer of technical information. Extralinguistic parameters of a technical text also include the surrounding text background – font size and color. Knowledge of these parameters and the ability to correctly decode and use them helps not only a technical specialist to successfully perform his duties, but also an ordinary person to successfully interact with machines and mechanisms, to understand innovation in the information technology age. Therefore, the analysis of non-verbal means in technical texts makes it possible to single out their main functions. Each non-verbal tool has its own function, but often these functions are intertwined due to the combination of elements. At the same time, not only the number of non-verbal means increases, but also the attractiveness of the text, because the general function of non-verbal means is to explain the verbal series. In the interaction of verbal and non-verbal means in the analyzed technical texts, the following general patterns have been revealed: parallel use of verbal and non-verbal elements to explain the text and create a coherent image; extensive use of graphs, diagrams, illustrations and other graphic elements (use of colors, fonts and formatting) to visualize information and facilitate its effective perception.